The Formulation of Cyber Responsibility Resonance Theory within the Framework of Criminal Law - Aryono Aryono; Yekti Mahardika (The Easta Journal Law and Human Rights, 2026)
The rapid advancement of information technology has given rise to increasingly complex, distributed, and transnational forms of cybercrime, thereby presenting new challenges to conventional concepts of criminal responsibility. This study aims to formulate the Cyber Responsibility Resonance Theory (CRRT) as a novel theoretical model in cybercriminal law that provides a more comprehensive framework for understanding liability within digital ecosystems. The research adopts a normative-conceptual method with a theoretical-constructive approach, drawing upon literature review and descriptive-interpretative qualitative analysis of Causality Theory, Network Society Theory, and Actor-Network Theory. The findings indicate that criminal responsibility in cyberspace is no longer linear or strictly individual, but is instead constituted through dynamic interactions among causality, digital networks, and resonance effects involving humans, technologies, and systems simultaneously. CRRT thus reconstructs the traditional paradigm of causal liability toward resonant liability, emphasizing distributed responsibility within interconnected digital networks. Case simulations further demonstrate that the impact of cybercrime may expand systemically, implicating not only primary perpetrators but also digital platforms and other network actors. Accordingly, CRRT contributes a conceptual advancement to cybercriminal law by offering a framework that is more adaptive, responsive, and aligned with the evolving nature of contemporary digital crime.